Validate an educative video for the promotion of the attachment between puerperal HIV-infected and their children. - Régia Christina Barbosa; Ana Karina Pinheiro (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
In front of the problematic the puerperal HIV-infected lives because of the virus of the human being immunodeficiency (HIV), we stand out the importance of the stimulation of the mother and baby pyschological bonding. The pyschological bonding is essential so that an effective bond is formed between the binomial. The considered objective of this study was: to validate an educative video for the promotion of the pyschological bonding between puerperal HIV-infected and their children. The development of the work occurred by the means of the construction of an educative video for the stimulation of the fondness, offering orientations for this clientele concerning the importance of the same, demonstrating that it is possible to develop it even being a soropositiva for the HIV. Until now, the stages of construction of the video had been carried through, as well as its appreciation by the technical and content judges. The data are being collected in the Clinic of Sexually Transmissible Illnesses of a public hospital of the city of Fortaleza that had begun in April 2008, with a foreseen date to be finished in September of the same year. It is worth to stand out that action had already the approval for the Committee of Ethics in Research of the Federal University of the Ceará. In the present study we are initiating the collection of data, that preliminarily comes demonstrating acceptance of the proposal on the part of the clientele and the involved professionals of health as a strong stimulator of the fondness between mother and son.